Evaluation of Crops in Agroforestry with Casuarina equisetifolia (Linn.) Plantations - Dagar, J.C.; Singh, Gurbachan (Indian Journal of Agroforestry, 2020)
For identification of crops in agroforestry with Casuarina equisetifolia plantations, a very good stand of six-years-old plantation having plant-to-plant and row-to-row distance of 6m x 6m, was selected in semi-arid region in Karnal, Haryana. Treatments such as removing of trees (alternate rows) in north-south and east-west directions creating partial shade, not removing trees at all having more shade, and crops without trees were imposed. To identify suitable crops for growing in interspaces of these plantations various combinations of crops viz. rice-wheat, blackgram (urd) - berseem, sorghum-lentil and c1usterbean (guar) – mustard during Kharif and Rabi seasons of first year while tuber crops turmeric, potato and taro (arvi) during second and third years were examined. During first year, it was found that growing traditional crops there was a reduction in yield of all the crops planted in inter-spaces of Casuarina plantations as compared with control (without plantation), though the reduction was less where the alternate rows of trees had been removed. But when tuber crops were grown, it was found that during first year the tuber yield was higher or at par under partial shade as compared to control (without plantation) but reduced abruptly under complete shade. During second year, the turmeric yield increased in partial shade while potato and taro yields declined slightly. There was, however, reduction in yield under complete shade. Thus, to grow tuber crops under partial shade with Casuarina is feasible and profitable.